Exploring the interconnection of social media, mental health and youth: A bibliometric analysis / Nurliyana Abas ... [et al.] - Abas, Nurliyana; Hussin, Hanani; Mohd Hardi, Norafiza; Hashim, Norhafizah (Research Management Centre (RMC), 2023)
This study explores social media, mental health, and youth interconnection and proposes potential future research directions. Utilising bibliometric analysis, we examined a selected set of 58 papers from the Scopus database, focusing on the study conducted between 2015 and 2022 that explored the interconnection of social media, mental health, and youth. We gained insights into the most significant contributions in this domain by assessing citations, publication locations, relevance within the research network, and influential articles and authors. Additionally, we conducted a thorough analysis of topics, identified barriers to expansion discussed in the literature, and recommended potential avenues for further investigation. The data was processed using the Publish or Perish software, while the researchers used a VOS viewer for data visualisation. Statistical analysis was performed using Microsoft Excel. The study presents a comprehensive bibliometric analysis, including trends in publication growth, research output, and citation analysis. Our search yielded 58 documents, with an increasing trend observed in studies on social media, mental health, and youth. English dominated most research papers, primarily published in journals and conference proceedings. The writers Moreno, M.A., Nicholas, J., Twenge, J.M., and Vishwakarma, D.K. are recognized as the most productive authors. The United States has emerged as the leading nation in publishing output. The survey lists the most significant academic centres, such as Florida State University, California State University, Fullerton, and the University of Pittsburgh School of Medicine. Two significant thematic clusters are revealed by keyword analysis: one focusing on the effects of the COVID-19 pandemic, internet use, and depression on young people's mental health, and the other investigating the relationships between elements like depressive symptoms, suicide, relationships, and social media use. The study suggests that theoretical frameworks like Social Cognitive Theory (SCT) and the Transactional Model of Stress and Coping can aid in understanding the mechanisms through which social media impacts mental health outcomes among youth. The practical implications of this analysis include the need for targeted interventions and support systems, such as digital literacy programs. The study underlines the necessity for continued research to improve our comprehension of how social media affects young people's mental health and to guide the creation of efficient interventions and regulations.